Early Cambrian U-Pb zircon age and Hf-isotope data from the Guasayán pluton, Sierras Pampeanas, Argentina: implications for the northwestern boundary of the Pampean arc - Dahlquist, Juan Andrés (2016)
An Early Cambrian pluton, known as the Guasayán pluton, has been identified in the central area of Sierra de Guasayán, northwestern Argentina. A U?Pb zircon Concordia age of 533 ± 4 Ma was obtained by LA-MC-ICP-MS and represents the first report of robustly dated Early Cambrian magmatism for the northwestern Sierras Pampeanas. The pluton was emplaced in low-grade metasedimentary rocks and its magmatic assemblage consists of K-feldspar (phenocrysts) + plagioclase + quartz + biotite, with zircon, apatite, ilmenite, magnetite and monazite as accessory minerals. Geochemically, the granitic rock is a metaluminous subalkaline felsic granodiorite with SiO2 = 69.24%, Na2O+ K2O = 7.08%, CaO = 2.45%, Na2O/ K2O = 0.71 and FeO/MgO = 3.58%. Rare earth element patterns show moderate slope (LaN/YbN = 8.05) with a slightly negative Eu anomalies (Eu/Eu* = 0.76). We report the first in situ Hf isotopes data (εHft = -0.12 to -4.76) from crystallized zircons in the Early Cambrian granites of the Sierras Pampeanas, helping to constrain the magma source and enabling comparison with other Pampean granites. The Guasayán pluton might provide a link between Early Cambrian magmatism of the central Sierras Pampeanas and that of the Eastern Cordillera, contributing to define the western boundary of the Pampean paleo-arc.